TP53 gene and p53 protein vs. endometrial carcinoma - Zając, Agnieszka; Stachowiak, Grzegorz; Stetkiewicz, Tomasz; R. Wilczyński, Jacek (Menopause Review/Przegląd Menopauzalny, 2013)
The TP53 gene and its protein p53 play an important role in the cell cycle, DNA repair and apoptosis initiation. Genetic anomalies of TP53 are related to some neoplasms, including endometrial cancer. These alterations may initiate cancerogenesis within endometrium, being observed in type II and poorly-differentiated carcinomas. Immunoexpression of TP53/p53 may be helpful in the diagnostic and therapeutic process and be a prognostic factor for this carcinoma.